#TITLE_ALTERNATIVE# - DWI ADITYA ( NIM : 20211312) Pembimbing : Widayani, Ph.D. ;Dr. rer.nat Sparisoma Viridi, IRFAN
Composite materials have many advantages because of the nature of composite materials that can be engineered as needed. Composite material composed of matrix that that serves as a matrix to transfer stress between the fiber reinforcement and also to protect the fiber from mechanical damage, and fiber as the reinforcement. This research was conducted to study the mechanical character of fiber aligned continuous composite, specifically on pressure test. The research was conducted through simulations and experimentations. The object tested in the research consisted of two fiber aligned continuous composite; composite with epoxy matrix & pencil carbon filler and with wood matrix & epoxy filler. The simulation was conducted using the Abaqus FEA 6.12 students edition software and utilizing the theory based on the “rule of mixtures”. For the experiment part, pressure tests were conducted to the composite object that has been made. Epoxy sample dimension created is 2 cm × 2 cm × 5 cm using fiber pencil rods as a fiber with diameter 0.2 cm. While the aligned continuous fiber composite model composite with wood matrix & epoxy filler has dimensions of 2.5 cm x 2.5 cm x 5 cm for the matrix and cylindrical fiber with a diameter of 0.5 cm and 5 cm length. v Simulations carried out using the same procedure with the compressive test procedure that is done by using Tensilon UCT-5T at P3FT LIPI Bandung by applying compressive test procedure with isostrain method, in which the matrix and fibers undergo the same length changes during testing. It appears that there is a difference between the simulation results with theoretical calculations. The more the number of fibers, the difference is even greater. It is very likely caused by the change in dimension of the fiber during the simulation process. To solve this problem, is to make just one fiber for different fiber volume fractions. Results of this simulation model is more in line with the theoretical picture. From the pressure tests, it was observed that the composite experienced bulging on the part which pressure was applied to by the pressure device. From the Micro CT scan result, we can see that in fact, the filler rods are broken everywhere The phenomena cannot seen by naked eyes. The result indicates that actually during the compression testing the response from the samples is only from the epoxy. Simulation study with epoxy matrix and pencil rods as a fiber shows that to improve the simulation, we add a brittle thin material to cover the upper part of the model. This thin material is stuck to the model. In the composite model with wood and fiber epoxy matrix seems that after a fully charged epoxy happened absorption by the wood so it looks like the epoxy volume decreases and therefore need the addition of a few times to meet them. Through this phenomenon is known that wood Albasiah have pores that can absorb epoxy. Based on visual observations and the observations using CT-scan on the composite model with albasiah matrix and epoxy fiber, during manufacturing process, epoxy absorption by wood phenomenon happen, and thus essentially a matrix that being used is not pure Albasiah wood, but Albasiah wood that has absorbed epoxy. While the results of the simulation show that the more the number of fibers, the volume of absorbed epoxy by the wood was more and more. vi Simulations also show that the distribution of the change in length (displacement) is greater at the top of the model or areas in direct contact with the pressure.